OP0195 Enhanced NLRP3-Dependent Interleukin-1B Secretion Correlates with Disease Activity in Pyogenic Sterile Arthritis Pyoderma Gangrenosum and Severe ACNE (PAPA) Syndrome. (9th June 2015) - Omenetti, A.; Carta, S.; Caorsi, R.; Delfino, L.; Penco, F.; Finetti, M.; Pastorino, C.; Martini, A.; Rubartelli, A.; Gattorno, M.
Abstract : Background: Positional differences of Proline-serine-threonine phosphatase-interacting protein 1 (PSTPIP1) mutations may trigger opposite clinical outcomes in Pyogenic sterile Arthritis Pyoderma gangrenosum and Acne (PAPA) syndorme. The typical triad may not be fully displayed, and clinical picture often vary along the disease history in the same individual. PSTPIP1-ASC-pyrin interaction may lead to caspase-1 dependent Interleukin (IL)1β secretion. However, the involvement of NLRP3 and IL1β signaling itself in PAPA were explored mostly in in vitro or in vivo systems. Furthermore, due to disease rarity, anti-IL1 effectiveness was unveiled or refuted based on brief clinical reports with significant variability in response to treatment. Differences in experimental conditions and assessments being performed in possibly differing stage of patients' diseases activity may give reason of the discrepancies observed. Thus, to date univocal insights concerning the actual role of IL1β signaling, its extent and the underlying regulatory molecular mechanisms in PAPA remain undefined, thus challenging an evidence-based application of anti-IL1 regimen. Objectives: To define whether IL1β secretion in PAPA syndrome (1) is enhanced, (2) requires NLRP3, and (3) correlates with different PSTPIP1 mutations, disease activity and/or clinical picture. Methods: A clinically well characterized cohort including 13 genetically confirmed PAPA subjects (E250Q+ N =10, E250K+ N =1, E256G+ N =2) and 1 patient wild-type (WT) for the common PSTPIP1 mutations were evaluated and compared with 35 healthy donors (HD). Peripheral blood monocytes were purified and studied at baseline and following in vitro TLR4 activation. Secretion pattern of IL1β, IL1α, IL1Ra, IL6, IL18 and Tumor Necrosis Factor (TNF)α was assessed in supernatants by ELISA and correlated to genotype, disease activity, ongoing therapies and clinical picture. Requirement of NLRP3 for IL1β secretion was investigated by silencing NLRP3 in monocytes purified from patients and HD. Results: Increased IL1β release was found in the overall PAPA cohort (P=0.254), and silencing of NLRP3 prevented it. Patients with active disease displayed higher IL1β oversecretion (P<0.01), and those with history of osteoarticular flares released more IL1β, IL6 and TNFα (P<0.05) compared to those with cutaneous recurrences. Anti-IL1 regimen reduced IL1β release and led to a complete control of osteoarticular lesions. A straightforward correlation between genotype and IL1β signaling was not observed. Conclusions: Variable IL1 β secretion was obserbed in PAPA cohort according to disease activity and clinical phenotype. The availability of a relevant number of patients and the chance to clinically and experimentally evaluate them in different phases of their disease history, allowed us to better define the actual behavior of IL1β secretion in this condition. Even if other mechanisms related to the complex PSTPISP1 protein networking might play additional roles, these results are in agreement with preliminary anecdotal reports on anti-IL1 regimen in PAPA and support the use of IL1 blockade as a potential effective therapeutic strategy in the clinical management of this condition. Disclosure of Interest: None declared